Direct-ink writing 3D printed energy storage devices: From material selectivity, design and optimization strategies to diverse applications. (April 2022) - Yan, Jin; Huang, Shaozhuan; Lim, Yew Von; Xu, Tingting; Kong, Dezhi; Li, Xinjian; Yang, Hui Ying; Wang, Ye
Graphical abstract: Abstract: Additive manufacturing, also known as three-dimensional (3D) printing technology, has recently emerged as a promising fabrication technology for a variety of applications with diverse complex architectures, as it allows for simple printing of desired pattern, fast prototyping, reduced fabrication process and low cost. As an important type of 3D printing technology, direct ink writing (DIW) endows the electrochemical energy storage devices (EESDs) with excellent electrochemical performance with high areal energy density and excellent rate capability owing to enhanced ion/electron transportation and surface kinetics induced by the designed patterns and device architecture. In view of the current infancy and urgency, as well as the lack of in-depth discussion, we critically overview the DIW 3D printing technology for EESDs devices in terms of materials selectivity principle for ink formulation and rheology, technical challenges (design principles and optimization strategies) and various EESDs applications in a comprehensive yet concise fashion. In this review, firstly, we introduce the typical features of DIW 3D printing technology. Subsequently, we discuss the design and optimization strategies towards several key parameters of DIW, including printable ink formulation, printing process and post treatment, device configuration and electrode pattern, porosity and tortuosity, as well as the package. Thereafter, we summarize the advances and recent progress of various EESDs devices fabricated by DIW technology, including conventional lithium/sodium ion batteries, newly emerged lithium sulfur/selenide/oxygen batteries, lithium/sodium-metal batteries, Ni-Fe batteries, zinc-air batteries, zinc ion batteries and supercapacitors, with a detailed analysis of rational design mechanism of each EESD. At last, the remaining challenges and research orientations in this booming field are proposed to motivate the future research and development of 3D printed EESDs.